Iron isotope exchange and fractionation between hematite (α-Fe2O3) and aqueous Fe(II): A combined three-isotope and reversal-approach to equilibrium study. (15th January 2019) - Frierdich, Andrew J.; Nebel, Oliver; Beard, Brian L.; Johnson, Clark M.
Abstract: Hematite is the most thermodynamically stable Fe oxide at the Earth's surface and its isotopic composition may record past biogeochemical Fe cycling and paleo-environmental conditions. Proper interpretation of its isotopic values requires an understanding of the equilibrium Fe isotope fractionation factor between hematite and other Fe-bearing minerals and aqueous species. Here, we use the three-isotope method ( 54 Fe- 56 Fe- 57 Fe, with 56 Fe/ 54 Fe and 57 Fe/ 56 Fe ratios expressed in delta notation relative to the IRMM-014 isotope standard) to simultaneously determine Fe isotope exchange, via tracking an enriched tracer-isotope (i.e. 57 Fe), and measure mass-dependent isotope fractionation between aqueous Fe(II) (Fe(II)aq ) with structural-Fe(III) in hematite, as determined from variations in 56 Fe/ 54 Fe ratios. Specifically, we used a reversal-approach to equilibrium by reacting three hematite samples of varying particle size and reactivity with two Fe(II)aq solutions that had initial 56 Fe/ 54 Fe ratios above and below the presumed equilibrium value. We confirm that Fe(II)aq readily exchanges with hematite at low temperature, and that the extent of exchange depends on hematite particle size. In three-isotope plots, δ 56 Fe values of Fe(II)aq exhibit unique trajectories depending on the initial hematite particle size. Rapid exchange occurring between Fe(II)aq and small hematite particles are affected by an apparent mixing reaction, which results in the δ 56 Fe value of Fe(II)aq to approach the isotopic composition of hematite. These trajectories exhibit inflections to more negative δ 56 Fe values during continued exchange. The location of these inflections depend on particle size and are interpreted to represent a change in the recrystallization mechanism from rapid "heterogeneous" recrystallization, which is limited to surface exchange, to "homogeneous" recrystallization involving the bulk hematite. Slow isotopic exchange occurring at longer reaction times appears to approximate equilibrium for all particle sizes with measured Fe(II)aq -hematite Fe isotope fractionation factors at 22 °C ranging from −2.61 ‰ (±0.26‰, 2σ) to −3.14 ‰ (±0.34‰, 2σ) in δ 56 Fe, and an average value of −2.8‰. This value is consistent with estimated fractionation factors measured during microbial Fe reduction experiments and with calculated and spectroscopically derived reduced partition function ratios. The three-isotope method provides a robust measure of equilibrium fractionation if proper constrains are utilized to eliminate extrapolation from partial exchange. Furthermore, it can provide insight into the mechanism of mineral-fluid exchange which is necessary for accurate quantification of the extent of mineral recrystallization when using isotopic tracers.